Politisierung der Kunst: Aids-Aktivismus in den USA - Hieber, Lutz (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1997)
AIDS Coalition To Unleash Power (ACT UP) was the most significant and forceful political movement in USA throughout the last decade. Its achievements are closely linked to the cultural conditions of its place of origin: the artistic Avantgarde in New York City. ACT UP’s concepts and starting points will be introduced. The discussion of this movement will also be used to throw a critical light on the political culture ofthe FRG.